Sigmoid volvulus: A pediatric case report and review of management - Lena M. O'Keefe; Yue-Yung Hu; Shefali Thaker; Christine Finck (Elsevier, 2016)
Volvulus in the pediatric population commonly occurs in the small bowel associated with malrotation or internal hernia whereas sigmoid volvulus (SV) is extremely rare. Herein we report a case of SV, review the literature and provide a suggested algorithm for diagnosis and management.